The Influence of Digital Technology on Marketing Strategy - Purnawati, Elisa (Penelitian dan Pengembangan Ilmu, 2024)
The alignment of Artificial Intelligence (AI) Technology in marketing has revolutionized market segmentation and marketing strategies. This paper examines the factors that influence the relationship between the use of AI in market segmentation and marketing strategy, including data and resource availability, organizational readiness and corporate culture, and legal and ethical considerations. Through a comprehensive literature review and analysis, this study identifies key hypotheses and discusses their implications for future research and practice. Despite challenges such as privacy concerns and ethical dilemmas, the integration of AI in marketing provides significant opportunities for enhanced customer experiences and better business performance.